Consumption Behavior of Khanom Jeen According to the Context of the Kao, Pa, Na, Lay Areas and Mueang District, Nakhon Si Thammarat Province - Wongwichian , Chantira; Limsuwanmanee, Jutaporn; Khongtong , Jatuporn (Journal of Nutrition Association of Thailand (Online), 2025)
This study aimed to explore the consumption behavior of Khanom jeen (fermented rice noodles) across various geographical and cultural contexts in Nakhon Si Thammarat Province, specifically in the areas defined as mountain area (Kao), forest area (Pa), field area (Na), coastal area (Lay), and the Mueang district. Data were collected from 768 consumers using a structured questionnaire and analyzed using descriptive statistics and Chi-square tests. The majority of consumers were female, aged 36–45, who preferred to eat Khanom jeen at restaurants with their families during lunchtime. Most consumers selected familiar establishments and placed high importance on traditional local flavors and side vegetables (Pak Nhor), particularly fermented or cooked vegetables such as coconut milk-boiled greens and pickles, which were more popular than fresh varieties. The study found statistically significant relationships between geographical and cultural context and certain consumption behaviors, including consumption frequency, ordering methods, and consumption time of day. However, preferences for taste and restaurant selection did not significantly differ across locations. The findings highlight the strong cultural roots of Khanom jeen consumption and suggest opportunities to support local food heritage through product development, such as health-focused side vegetables sets (Pak Nhor), which gained high consumer interest. This research provides valuable insights for preserving food culture, promoting local economies, and developing products and services that align with regional lifestyles in a sustainable manner. Please read and correct proof of this abstract.